(3GdNWC GdYbOj hBKGQ GdYbOs - (3eQhGf(B, (3cSGHs ([(3O(B.(3e(B.]:s (3eWGHY hGcO(B,s, 2000)
(3JYQja BKGQ GdYbO hGdJejjRjf CKQ GdehLH hCKQ GdYbO hGdGOGQI GdHGWfjI hGdGOGQI GdXGgQI, GdePgH GddGJjfj hGdePgH GdCdeGfj, GdePgH GdaQOj hGdePgH GdGLJeGYj, eHOC fSHjI GdYbhO, JaSjQ GdYbO HGdfSHI ddehVhY, JMOjO eOi GdehLHGJ GdfGTFI YfO GdYbO, JfajO GdYbO Ch GdLRGA GdeJQJH Ydjg, eSCdI JMQjQ fWGb GdYbO, BKGQ GdYbO HGdfSHI ddGTNGU, fXQjI GdJYGbO deUdMI GdZjQ, eaghe GdYbO aj GWGQ GdbGfhf GdeOfj hGdMGdGJ GdYdejI ddJYgO Yf GdZjQ, fXQjI GdMhGOK GdWGQFIs
(3GdeQGLY U(B.149s
Keywords: (3GdYbhOs; (3GdbGfhf GdeOfjs